2013
DOI: 10.6018/analesps.29.2.131381
|View full text |Cite
|
Sign up to set email alerts
|

La exposición de los menores a la pornografía en Internet: prevalencia, motivaciones, contenidos y efectos

Abstract: Título: La exposición de los menores a la pornografía en Internet: prevalencia, motivaciones, contenidos y efectos. Resumen: En virtud del aumento de la disponibilidad de material pornográfico en Internet, ha surgido la necesidad de investigar las característi-cas y consecuencias de la exposición de los niños y adolescentes a este tipo de material. Partiendo de informes retrospectivos de una muestra de 494 estudiantes de la Universidad de Salamanca recogidos con una encuesta online, este estudio analiza la pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Pornographic is mostly perpetrated by adolescent boys than adolescent girls so that male teenagers are more susceptible to the influence of sex material and act as perpetrators of spreading pornography. These results are in line with Ortega and Baz (2013) studies that find in Spain that teenagers have higher levels of pornography exported either intentional or unintentional. Prichard et al (2013) suggests that boys more often remember the reaction of porn content to sexual arousal while girls are more avoiding.…”
Section: Discussionsupporting
confidence: 92%
“…Pornographic is mostly perpetrated by adolescent boys than adolescent girls so that male teenagers are more susceptible to the influence of sex material and act as perpetrators of spreading pornography. These results are in line with Ortega and Baz (2013) studies that find in Spain that teenagers have higher levels of pornography exported either intentional or unintentional. Prichard et al (2013) suggests that boys more often remember the reaction of porn content to sexual arousal while girls are more avoiding.…”
Section: Discussionsupporting
confidence: 92%
“…Multigroup invariance testing showed that the model tested in this study did not apply equally across genders with the model applying to males more so than females. First, males tend to pursue more varied sexual experiences (Oshri, Tubman, Morganlopez, Saavedra, & Csizmadia, 2013); they also report more sexual arousal (Goodson, McCormick, & Evans, 2000), sexual excitement, and masturbation when browsing pornographic materials online with females reporting more avoidance, disgust, or worries (González-Ortega & Orgaz-Baz, 2013). Therefore, males, particularly those high in SSS, may be more likely to seek novel sexual stimulation online that may lead to PIPU.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, males, particularly those high in SSS, may be more likely to seek novel sexual stimulation online that may lead to PIPU. Second, emotional factors may be more important in relation to sexual behaviors for females when compared to males (Cooper, Morahan-Martin, Mathy, & Maheu, 2002), but most sexual explicit materials available online may be less desirable for females (Gonzalez-Ortega & Orgaz-Baz, 2013). Finally, women also in general view pornography more negatively than men (Malamuth, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…One study consisting of young adults (ages 17 to 20) found that 4.2 % of the sample had viewed CP [14]. In a university sample, 7.6 % of students reported viewing CP in the past [15]. Although the prevalence of CP use in the general population is estimated to be at these rates, it is not possible to know whether those convicted or charged with CP-related offenses are reflective of this prevalence.…”
Section: The Role Of the Internet In Sex Crime Ratesmentioning
confidence: 87%